Pandemic Preparedness Against Influenza: DNA Vaccine for Rapid Relief - Andersen, Tor Kristian; Bodin, Johanna; Oftung, Fredrik; Bogen, Bjarne; Mjaaland, Siri; Grødeland, Gunnveig (Frontiers in Immunology, 2021)
The 2009 “swine flu” pandemic outbreak demonstrated the limiting capacity for egg-based vaccines with respect to global vaccine supply within a timely fashion. New vaccine platforms that efficiently can quench pandemic influenza emergences are urgently needed. Since 2009, there has been a profound development of new vaccine platform technologies with respect to prophylactic use in the population, including DNA vaccines. These vaccines are particularly well suited for global pandemic responses as the DNA format is temperature stable and the production process is cheap and rapid. Here, we show that by targeting influenza antigens directly to antigen presenting cells (APC), DNA vaccine efficacy equals that of conventional technologies. A single dose of naked DNA encoding hemagglutinin (HA) from influenza/A/California/2009 (H1N1), linked to a targeting moiety directing the vaccine to major histocompatibility complex class II (MHCII) molecules, raised similar humoral immune responses as the adjuvanted split virion vaccine Pandemrix, widely administered in the 2009 pandemic. Both vaccine formats rapidly induced serum antibodies that could protect mice already 8 days after a single immunization, in contrast to the slower kinetics of a seasonal trivalent inactivated influenza vaccine (TIV). Importantly, the DNA vaccine also elicited cytotoxic T-cell responses that reduced morbidity after vaccination, in contrast to very limited T-cell responses seen after immunization with Pandemrix and TIV. These data demonstrate that DNA vaccines has the potential as a single dose platform vaccine, with rapid protective effects without the need for adjuvant, and confirms the relevance of naked DNA vaccines as candidates for pandemic preparedness.